Glycomic Analysis of Life Stages of the Human Parasite Schistosoma mansoni Reveals Developmental Expression Profiles of Functional and Antigenic Glycan Motifs* - Cornelis H. Smit; Angela van Diepen; D. Linh Nguyen; Manfred Wuhrer; Karl F. Hoffmann; André M. Deelder; Cornelis H. Hokke (2015)
Glycans present on glycoproteins and glycolipids of the major human parasite Schistosoma mansoni induce innate as well as adaptive immune responses in the host. To be able to study the molecular characteristics of schistosome infections it is therefore required to determine the expression profiles of glycans and antigenic glycan-motifs during a range of critical stages of the complex schistosome lifecycle. We performed a longitudinal profiling study covering schistosome glycosylation throughout worm- and egg-development using a mass spectrometry-based glycomics approach. Our study revealed that during worm development N-glycans with Galβ1–4(Fucα1–3)GlcNAc (LeX) and core-xylose motifs were rapidly lost after cercariae to schistosomula transformation, whereas GalNAcβ1–4GlcNAc (LDN)-motifs gradually became abundant and predominated in adult worms. LeX-motifs were present on glycolipids up to 2 weeks of schistosomula development, whereas glycolipids with mono- and multifucosylated LDN-motifs remained present up to the adult worm stage. In contrast, expression of complex O-glycans diminished to undetectable levels within days after transformation. During egg development, a rich diversity of N-glycans with fucosylated motifs was expressed, but with α3-core fucose and a high degree of multifucosylated antennae only in mature eggs and miracidia. N-glycan antennae were exclusively LDN-based in miracidia. O-glycans in the mature eggs were also diverse and contained LeX- and multifucosylated LDN, but none of these were associated with miracidia in which we detected only the Galβ1–3(Galβ1–6)GalNAc core glycan. Immature eggs also exhibited short O-glycan core structures only, suggesting that complex fucosylated O-glycans of schistosome eggs are derived primarily from glycoproteins produced by the subshell envelope in the developed egg. Lipid glycans with multifucosylated GlcNAc repeats were present throughout egg development, but with the longer highly fucosylated stretches enriched in mature eggs and miracidia. This global analysis of the developing schistosome's glycome provides new insights into how stage-specifically expressed glycans may contribute to different aspects of schistosome-host interactions. Glycans present on glycoproteins and glycolipids of the major human parasite Schistosoma mansoni induce innate as well as adaptive immune responses in the host. To be able to study the molecular characteristics of schistosome infections it is therefore required to determine the expression profiles of glycans and antigenic glycan-motifs during a range of critical stages of the complex schistosome lifecycle. We performed a longitudinal profiling study covering schistosome glycosylation throughout worm- and egg-development using a mass spectrometry-based glycomics approach. Our study revealed that during worm development N-glycans with Galβ1–4(Fucα1–3)GlcNAc (LeX) and core-xylose motifs were rapidly lost after cercariae to schistosomula transformation, whereas GalNAcβ1–4GlcNAc (LDN)-motifs gradually became abundant and predominated in adult worms. LeX-motifs were present on glycolipids up to 2 weeks of schistosomula development, whereas glycolipids with mono- and multifucosylated LDN-motifs remained present up to the adult worm stage. In contrast, expression of complex O-glycans diminished to undetectable levels within days after transformation. During egg development, a rich diversity of N-glycans with fucosylated motifs was expressed, but with α3-core fucose and a high degree of multifucosylated antennae only in mature eggs and miracidia. N-glycan antennae were exclusively LDN-based in miracidia. O-glycans in the mature eggs were also diverse and contained LeX- and multifucosylated LDN, but none of these were associated with miracidia in which we detected only the Galβ1–3(Galβ1–6)GalNAc core glycan. Immature eggs also exhibited short O-glycan core structures only, suggesting that complex fucosylated O-glycans of schistosome eggs are derived primarily from glycoproteins produced by the subshell envelope in the developed egg. Lipid glycans with multifucosylated GlcNAc repeats were present throughout egg development, but with the longer highly fucosylated stretches enriched in mature eggs and miracidia. This global analysis of the developing schistosome's glycome provides new insights into how stage-specifically expressed glycans may contribute to different aspects of schistosome-host interactions. Schistosoma blood flukes give rise to infections in over 200 million people in developing countries worldwide (1.Gryseels B. Polman K. Clerinx J. Kestens L. Human schistosomiasis.Lancet. 2006; 368: 1106-1118Abstract Full Text Full Text PDF PubMed Scopus (1585) Google Scholar). With a Disability-Adjusted Life Years (DALY) value of more than 3 million, schistosomiasis ranks as one of the neglected tropical diseases with the highest impact on public health (2.King C.H. Health metrics for helminth infections.Acta Trop. 2015; 141: 150-160Crossref PubMed Scopus (45) Google Scholar). The schistosome has a complex and intriguing lifecycle, which involves a definitive host (mammal) as well as an intermediate host (snail). Infections with Schistosoma mansoni, one of the major schistosome species infecting humans, are initiated when snail-borne cercariae penetrate intact skin. The cercariae then transform into schistosomula, which enter the vasculature of the host and mature while migrating to the portal system. Here, adult male and female worms pair, with the female worm producing hundreds of eggs each day during a life span of several years unless the infection is treated by chemotherapy. Miracidia develop inside the maturing eggs while they cross the intestinal wall over a period of several days to be excreted with the feces. Miracidia then hatch from the eggs upon contact with fresh water and infect the snail host where asexual replication takes place and eventually new cercariae are shed. Notably, many eggs get trapped in organs such as the liver, where they induce a granulomatous inflammation and organ damage, the main cause of pathology in schistosomiasis (1.Gryseels B. Polman K. Clerinx J. Kestens L. Human schistosomiasis.Lancet. 2006; 368: 1106-1118Abstract Full Text Full Text PDF PubMed Scopus (1585) Google Scholar). Throughout their lifecycle, schistosomes express a multitude of protein- and lipid-linked glycans that play an important role in the parasite biology. The expression of many glycan elements appears to be developmentally regulated by the differential expression of glycosyltransferases during the different lifecycle stages (3.Fitzpatrick J.M. Peak E. Perally S. Chalmers I.W. Barrett J. Yoshino T.P. Ivens A.C. Hoffmann K.F. Antischistosomal intervention targets identified by lifecycle transcriptomic analyses.PLoS. Negl. Trop. Dis. 2009; 3: e543Crossref PubMed Scopus (103) Google Scholar). A series of papers has been published indicating that schistosome glycans play essential roles in the molecular interaction of the parasite and the host immune system, enabling survival of the parasite and allowing chronic infection to establish. For example, glycosylated soluble egg antigens (SEA) interact with the C-type lectins mannose receptor (MR), macrophage galactose-type lectin (MGL) and dendritic cell-specific ICAM-3-grabbing nonintegrin (DC-SIGN), and some of these interactions lead to immunomodulatory effects of specific components of SEA via dendritic cells (DCs) [1]The abbreviations used are:DCdendritic cellMRmannose receptorMGLmacrophage galactose-type lectinDC-SIGNdendritic cell-specific ICAM-3-grabbing nonintegrinTh2T helper 2FFuc or fucoseDFdifucosyl or Fucα1–2Fucα1–3TFtrifucosyl or Fucα1–2Fucα1–2Fucα1–3HHex or hexoseNHexNAc or N-acetylhexosamineXXyl or xyloseGalGalactoseGalNAcN-acetylgalactosamineGlcNAcN-acetylglucosamineLDNLacDiNAc or GalNAcβ1–4GlcNAcLNLacNAc or Galβ1–4GlcNAcLeXLewis X or Galβ1–4(Fucα1–3)GlcNAcLDN-FGalNAcβ1–4(Fucα1–3)GlcNAcF-LDN-FFucα1–3GalNAcβ1–4(Fucα1–3)GlcNAcF-LDNFucα1–3GalNAcβ1–4GlcNAcPseudo-LeYpseudo Lewis Y or Fucα1–3Galβ1–4(Fucα1–3)GlcNAc)CAAcirculating anodic antigenCCAcirculating cathodic antigenSEAsoluble egg antigensIPSEinterleukin-4-inducing principle from schistosome eggsPNGase FN-glycosidase FPNGase AN-glycosidase ArEGCase IIrecombinant endoglycoceramidase IINAGβ-N-acetylglucosaminidase from jack beanBKFα-L-fucosidase from bovine kidneyXMFα(1–3,4)-fucosidase from Xanthomonas manihotisJBGβ(1–4,6)-galactosidase from jack bean2-AA2-aminobenzoic acidDHB2,5-dihydroxybenzoic acidNMRnuclear magnetic resonanceRPreversed phaseMeOHmethanolESexcretory secretory molecules. [1]The abbreviations used are:DCdendritic cellMRmannose receptorMGLmacrophage galactose-type lectinDC-SIGNdendritic cell-specific ICAM-3-grabbing nonintegrinTh2T helper 2FFuc or fucoseDFdifucosyl or Fucα1–2Fucα1–3TFtrifucosyl or Fucα1–2Fucα1–2Fucα1–3HHex or hexoseNHexNAc or N-acetylhexosamineXXyl or xyloseGalGalactoseGalNAcN-acetylgalactosamineGlcNAcN-acetylglucosamineLDNLacDiNAc or GalNAcβ1–4GlcNAcLNLacNAc or Galβ1–4GlcNAcLeXLewis X or Galβ1–4(Fucα1–3)GlcNAcLDN-FGalNAcβ1–4(Fucα1–3)GlcNAcF-LDN-FFucα1–3GalNAcβ1–4(Fucα1–3)GlcNAcF-LDNFucα1–3GalNAcβ1–4GlcNAcPseudo-LeYpseudo Lewis Y or Fucα1–3Galβ1–4(Fucα1–3)GlcNAc)CAAcirculating anodic antigenCCAcirculating cathodic antigenSEAsoluble egg antigensIPSEinterleukin-4-inducing principle from schistosome eggsPNGase FN-glycosidase FPNGase AN-glycosidase ArEGCase IIrecombinant endoglycoceramidase IINAGβ-N-acetylglucosaminidase from jack beanBKFα-L-fucosidase from bovine kidneyXMFα(1–3,4)-fucosidase from Xanthomonas manihotisJBGβ(1–4,6)-galactosidase from jack bean2-AA2-aminobenzoic acidDHB2,5-dihydroxybenzoic acidNMRnuclear magnetic resonanceRPreversed phaseMeOHmethanolESexcretory secretory molecules. (4.van Liempt E. van Vliet S.J. Engering A. Garcia Vallejo J.J. Bank C.M. Sanchez-Hernandez M. van K.Y. van I., D. Schistosoma mansoni soluble egg antigens are internalized by human dendritic cells through multiple C-type lectins and suppress TLR-induced dendritic cell activation.Mol. Immunol. 2007; 44: 2605-2615Crossref PubMed Scopus (209) Google Scholar, 5.Everts B. Hussaarts L. Driessen N.N. Meevissen M.H. Schramm G. van der Ham A.J. van der Hoeven B. Scholzen T. Burgdorf S. Mohrs M. Pearce E.J. Hokke C.H. Haas H. Smits H.H. Yazdanbakhsh M. Schistosome-derived omega-1 drives Th2 polarization by suppressing protein synthesis following internalization by the mannose receptor.J. Exp. Med. 2012; 209: 1753-1767Crossref PubMed Scopus (185) Google Scholar). Furthermore, fucosylated egg glycolipids trigger innate immune responses of peripheral blood mononuclear cells and egg glycans are required for periovular granuloma formation in a mouse model. In addition, cercarial secretions induce alternatively activated macrophages in a carbohydrate dependent manner (6.van der Kleij D. van Remoortere A. Schuitemaker J.H. Kapsenberg M.L. Deelder A.M. Tielens A.G. Hokke C.H. Yazdanbakhsh M. Triggering of innate immune responses by schistosome egg glycolipids and their carbohydrate epitope GalNAc beta 1–4(Fuc alpha 1–2Fuc alpha 1–3)GlcNAc.J. Infect. Dis. 2002; 185: 531-539Crossref PubMed Scopus (88) Google Scholar, 7.Van de Vijver K.K. Hokke C.H. van Remoortere A. Jacobs W. Deelder A.M. Van Marck E.A. Glycans of Schistosoma mansoni and keyhole limpet haemocyanin induce hepatic granulomas in vivo.Int. J. Parasitol. 2004; 34: 951-961Crossref PubMed Scopus (32) Google Scholar, 8.Van de Vijver K.K. Deelder A.M. Jacobs W. Van Marck E.A. Hokke C.H. LacdiNAc- and LacNAc-containing glycans induce granulomas in an in vivo model for schistosome egg-induced hepatic granuloma formation.Glycobiology. 2006; 16: 237-243Crossref PubMed Scopus (46) Google Scholar, 9.Jenkins S.J. Hewitson J.P. Ferret-Bernard S. Mountford A.P. Schistosome larvae stimulate macrophage cytokine production through TLR4-dependent and –independent pathways.Int. Immunol. 2005; 17: 1409-1418Crossref PubMed Scopus (68) Google Scholar). Importantly, also adaptive immune responses to schistosome glycans are mounted by the human host. A large part of the antibody responses to schistosomes is directed against antigenic glycan motifs, raising the question whether they could form a basis for antischistosome vaccine strategies (10.Omer-Ali P. Magee A.I. Kelly C. Simpson A.J. A major role for carbohydrate epitopes preferentially recognized by chronically infected mice in the determination of Schistosoma mansoni schistosomulum surface antigenicity.J. Immunol. 1986; 137: 3601-3607PubMed Google Scholar). dendritic cell mannose receptor macrophage galactose-type lectin dendritic cell-specific ICAM-3-grabbing nonintegrin T helper 2 Fuc or fucose difucosyl or Fucα1–2Fucα1–3 trifucosyl or Fucα1–2Fucα1–2Fucα1–3 Hex or hexose HexNAc or N-acetylhexosamine Xyl or xylose Galactose N-acetylgalactosamine N-acetylglucosamine LacDiNAc or GalNAcβ1–4GlcNAc LacNAc or Galβ1–4GlcNAc Lewis X or Galβ1–4(Fucα1–3)GlcNAc GalNAcβ1–4(Fucα1–3)GlcNAc Fucα1–3GalNAcβ1–4(Fucα1–3)GlcNAc Fucα1–3GalNAcβ1–4GlcNAc pseudo Lewis Y or Fucα1–3Galβ1–4(Fucα1–3)GlcNAc) circulating anodic antigen circulating cathodic antigen soluble egg antigens interleukin-4-inducing principle from schistosome eggs N-glycosidase F N-glycosidase A recombinant endoglycoceramidase II β-N-acetylglucosaminidase from jack bean α-L-fucosidase from bovine kidney α(1–3,4)-fucosidase from Xanthomonas manihotis β(1–4,6)-galactosidase from jack bean 2-aminobenzoic acid 2,5-dihydroxybenzoic acid nuclear magnetic resonance reversed phase methanol excretory secretory molecules. dendritic cell mannose receptor macrophage galactose-type lectin dendritic cell-specific ICAM-3-grabbing nonintegrin T helper 2 Fuc or fucose difucosyl or Fucα1–2Fucα1–3 trifucosyl or Fucα1–2Fucα1–2Fucα1–3 Hex or hexose HexNAc or N-acetylhexosamine Xyl or xylose Galactose N-acetylgalactosamine N-acetylglucosamine LacDiNAc or GalNAcβ1–4GlcNAc LacNAc or Galβ1–4GlcNAc Lewis X or Galβ1–4(Fucα1–3)GlcNAc GalNAcβ1–4(Fucα1–3)GlcNAc Fucα1–3GalNAcβ1–4(Fucα1–3)GlcNAc Fucα1–3GalNAcβ1–4GlcNAc pseudo Lewis Y or Fucα1–3Galβ1–4(Fucα1–3)GlcNAc) circulating anodic antigen circulating cathodic antigen soluble egg antigens interleukin-4-inducing principle from schistosome eggs N-glycosidase F N-glycosidase A recombinant endoglycoceramidase II β-N-acetylglucosaminidase from jack bean α-L-fucosidase from bovine kidney α(1–3,4)-fucosidase from Xanthomonas manihotis β(1–4,6)-galactosidase from jack bean 2-aminobenzoic acid 2,5-dihydroxybenzoic acid nuclear magnetic resonance reversed phase methanol excretory secretory molecules. Rapid developments in mass spectrometry-based glycan-analysis technology in the last two decades have led to several studies focused on elucidating the glycan structures of somatic and secretory schistosome preparations (11.Wuhrer M. Koeleman C.A. Fitzpatrick J.M. Hoffmann K.F. Deelder A.M. Hokke C.H. Gender-specific expression of complex-type N-glycans in schistosomes.Glycobiology. 2006; 16: 991-1006Crossref PubMed Scopus (50) Google Scholar, 12.Khoo K.H. Sarda S. Xu X. Caulfield J.P. McNeil M.R. Homans S.W. Morris H.R. Dell A. A unique multifucosylated -3GalNAc beta 1–>4GlcNAc beta 1–>3Gal alpha 1- motif constitutes the repeating unit of the complex O-glycans derived from the cercarial glycocalyx of Schistosoma mansoni.J. Biol. Chem. 1995; 270: 17114-17123Abstract Full Text Full Text PDF PubMed Scopus (115) Google Scholar, 13.Khoo K.H. Chatterjee D. Caulfield J.P. Morris H.R. Dell A. Structural mapping of the glycans from the egg glycoproteins of Schistosoma mansoniSchistosoma japonicum: identification of novel core structures and terminal sequences.Glycobiology. 1997; 7: 663-677Crossref PubMed Scopus (117) Google Scholar, 14.Huang H.H. Tsai P.L. Khoo K.H. Selective expression of different fucosylated epitopes on two distinct sets of Schistosoma mansoni cercarial O-glycans: identification of a novel core type and Lewis X structure.Glycobiology. 2001; 11: 395-406Crossref PubMed Scopus (48) Google Scholar, 15.Khoo K.H. Huang H.H. Lee K.M. Characteristic structural features of schistosome cercarial N-glycans: expression of Lewis X and core xylosylation.Glycobiology. 2001; 11: 149-163Crossref PubMed Scopus (57) Google Scholar, 16.Wuhrer M. Koeleman C.A. Deelder A.M. Hokke C.H. Repeats of LacdiNAc and fucosylated LacdiNAc on N-glycans of the human parasite Schistosoma mansoni.FEBS J. 2006; 273: 347-361Crossref PubMed Scopus (62) Google Scholar, 17.Jang-Lee J. Curwen R.S. Ashton P.D. Tissot B. Mathieson W. Panico M. Dell A. Wilson R.A. Haslam S.M. Glycomics analysis of Schistosoma mansoni egg and cercarial secretions.Mol. Cell. Proteomics. 2007; 6: 1485-1499Abstract Full Text Full Text PDF PubMed Scopus (95) Google Scholar, 18.Frank S. van Die I. Geyer R. Structural characterization of Schistosoma mansoni adult worm glycosphingolipids reveals pronounced differences with those of cercariae.Glycobiology. 2012; 22: 676-695Crossref PubMed Scopus (16) Google Scholar, 19.Wuhrer M. Kantelhardt S.R. Dennis R.D. Doenhoff M.J. Lochnit G. Geyer R. Characterization of glycosphingolipids from Schistosoma mansoni eggs carrying Fuc(alpha1–3)GalNAc-, GalNAc(beta1–4)[Fuc(alpha1–3)]GlcNAc- and Gal(beta1–4)[Fuc(alpha1–3)]GlcNAc- (Lewis X) terminal structures.Eur. J. Biochem. 2002; 269: 481-493Crossref PubMed Scopus (62) Google Scholar, 20.Hokke C.H. Deelder A.M. Hoffmann K.F. Wuhrer M. Glycomics-driven discoveries in schistosome research.Exp. Parasitol. 2007; 117: 275-283Crossref PubMed Scopus (70) Google Scholar, 21.Khoo K.H. Chatterjee D. Caulfield J.P. Morris H.R. Dell A. Structural characterization of glycophingolipids from the eggs of Schistosoma mansoniSchistosoma japonicum.Glycobiology. 1997; 7: 653-661Crossref PubMed Scopus (71) Google Scholar, 22.Wuhrer M. Dennis R.D. Doenhoff M.J. Lochnit G. Geyer R. Schistosoma mansoni cercarial glycolipids are dominated by Lewis X and pseudo-Lewis Y structures.Glycobiology. 2000; 10: 89-101Crossref PubMed Scopus (76) Google Scholar). Among the typical glycan elements detected in S. mansoni were unusual and antigenic Fucα1–2Fucα1–3- (DF-) motifs attached to GalNAcβ1–4GlcNAc (LacDiNAc or LDN) (12.Khoo K.H. Sarda S. Xu X. Caulfield J.P. McNeil M.R. Homans S.W. Morris H.R. Dell A. A unique multifucosylated -3GalNAc beta 1–>4GlcNAc beta 1–>3Gal alpha 1- motif constitutes the repeating unit of the complex O-glycans derived from the cercarial glycocalyx of Schistosoma mansoni.J. Biol. Chem. 1995; 270: 17114-17123Abstract Full Text Full Text PDF PubMed Scopus (115) Google Scholar, 14.Huang H.H. Tsai P.L. Khoo K.H. Selective expression of different fucosylated epitopes on two distinct sets of Schistosoma mansoni cercarial O-glycans: identification of a novel core type and Lewis X structure.Glycobiology. 2001; 11: 395-406Crossref PubMed Scopus (48) Google Scholar, 17.Jang-Lee J. Curwen R.S. Ashton P.D. Tissot B. Mathieson W. Panico M. Dell A. Wilson R.A. Haslam S.M. Glycomics analysis of Schistosoma mansoni egg and cercarial secretions.Mol. Cell. Proteomics. 2007; 6: 1485-1499Abstract Full Text Full Text PDF PubMed Scopus (95) Google Scholar, 18.Frank S. van Die I. Geyer R. Structural characterization of Schistosoma mansoni adult worm glycosphingolipids reveals pronounced differences with those of cercariae.Glycobiology. 2012; 22: 676-695Crossref PubMed Scopus (16) Google Scholar, 19.Wuhrer M. Kantelhardt S.R. Dennis R.D. Doenhoff M.J. Lochnit G. Geyer R. Characterization of glycosphingolipids from Schistosoma mansoni eggs carrying Fuc(alpha1–3)GalNAc-, GalNAc(beta1–4)[Fuc(alpha1–3)]GlcNAc- and Gal(beta1–4)[Fuc(alpha1–3)]GlcNAc- (Lewis X) terminal structures.Eur. J. Biochem. 2002; 269: 481-493Crossref PubMed Scopus (62) Google Scholar, 21.Khoo K.H. Chatterjee D. Caulfield J.P. Morris H.R. Dell A. Structural characterization of glycophingolipids from the eggs of Schistosoma mansoniSchistosoma japonicum.Glycobiology. 1997; 7: 653-661Crossref PubMed Scopus (71) Google Scholar), Xylβ1–2- and Fucα1–3-modified N-glycan core structures (13.Khoo K.H. Chatterjee D. Caulfield J.P. Morris H.R. Dell A. Structural mapping of the glycans from the egg glycoproteins of Schistosoma mansoniSchistosoma japonicum: identification of novel core structures and terminal sequences.Glycobiology. 1997; 7: 663-677Crossref PubMed Scopus (117) Google Scholar, 15.Khoo K.H. Huang H.H. Lee K.M. Characteristic structural features of schistosome cercarial N-glycans: expression of Lewis X and core xylosylation.Glycobiology. 2001; 11: 149-163Crossref PubMed Scopus (57) Google Scholar, 17.Jang-Lee J. Curwen R.S. Ashton P.D. Tissot B. Mathieson W. Panico M. Dell A. Wilson R.A. Haslam S.M. Glycomics analysis of Schistosoma mansoni egg and cercarial secretions.Mol. Cell. Proteomics. 2007; 6: 1485-1499Abstract Full Text Full Text PDF PubMed Scopus (95) Google Scholar, 20.Hokke C.H. Deelder A.M. Hoffmann K.F. Wuhrer M. Glycomics-driven discoveries in schistosome research.Exp. Parasitol. 2007; 117: 275-283Crossref PubMed Scopus (70) Google Scholar), and a unique O-glycan core (Galβ1–3(Galβ1–6)GalNAc) (14.Huang H.H. Tsai P.L. Khoo K.H. Selective expression of different fucosylated epitopes on two distinct sets of Schistosoma mansoni cercarial O-glycans: identification of a novel core type and Lewis X structure.Glycobiology. 2001; 11: 395-406Crossref PubMed Scopus (48) Google Scholar, 17.Jang-Lee J. Curwen R.S. Ashton P.D. Tissot B. Mathieson W. Panico M. Dell A. Wilson R.A. Haslam S.M. Glycomics analysis of Schistosoma mansoni egg and cercarial secretions.Mol. Cell. Proteomics. 2007; 6: 1485-1499Abstract Full Text Full Text PDF PubMed Scopus (95) Google Scholar) (see supplemental Table S5 for a definition of glycan motifs of S. mansoni glycoconjugates). Also more widely occurring glycan elements shared with the mammalian or snail host were detected, e.g. Galβ1–4GlcNAc (LacNAc or LN), Galβ1–4(Fucα1–3)GlcNAc (Lewis X or LeX), LDN, and GalNAcβ1–4(Fucα1–3)GlcNAc (LDN-F) (23.Fox N. Damjanov I. Knowles B.B. Solter D. Immunohistochemical localization of the mouse stage-specific embryonic antigen 1 in human tissues and tumors.Cancer Res. 1983; 43: 669-678PubMed Google Scholar, 24.Bergwerff A.A. Thomas-Oates J.E. van Oostrum J. Kamerling J.P. Vliegenthart J.F. Human urokinase contains GalNAc beta (1–4)[Fuc alpha (1–3)]GlcNAc beta (1–2) as a novel terminal element in N-linked carbohydrate chains.FEBS Lett. 1992; 314: 389-394Crossref PubMed Scopus (56) Google Scholar). These data were generated over a long period of time, often focusing on a single schistosome life stage and a specific class of glycans only, and using various analytical techniques and strategies that make inter-study comparisons often difficult. In addition, glycosylation of the schistosomula that develop shortly after infection and are considered to be relatively vulnerable to immune attack, has remained largely unexplored (20.Hokke C.H. Deelder A.M. Hoffmann K.F. Wuhrer M. Glycomics-driven discoveries in schistosome research.Exp. Parasitol. 2007; 117: 275-283Crossref PubMed Scopus (70) Google Scholar, 25.Nyame A.K. Kawar Z.S. Cummings R.D. Antigenic glycans in parasitic infections: implications for vaccines and diagnostics.Arch. Biochem. Biophys. 2004; 426: 182-200Crossref PubMed Scopus (131) Google Scholar, 26.Nyame A.K. Lewis F.A. Doughty B.L. Correa-Oliveira R. Cummings R.D. Immunity to schistosomiasis: glycans are potential antigenic targets for immune intervention.Exp. Parasitol. 2003; 104: 1-13Crossref PubMed Scopus (81) Google Scholar), although these could be interesting therapeutic targets (27.Butterworth A.E. Dunne D.W. Fulford A.J. Thorne K.J. Gachuhi K. Ouma J.H. Sturrock R.F. Human immunity to Schistosoma mansoni: observations on mechanisms, and implications for control.Immunol. Invest. 1992; 21: 391-407Crossref PubMed Scopus (77) Google Scholar, 28.Capron M. Capron A. Rats, mice, and men – models for immune effector mechanisms against schistosomiasis.Parasitol. Today. 1986; 2: 69-75Abstract Full Text PDF PubMed Scopus (93) Google Scholar, 29.Araujo J.M. Melo T.T. Sena I.C. Alves C.C. Araujo N. Duraes F. V Oliveira S.C. Fonseca C.T. Schistosoma mansoni schistosomula tegument (Smteg) immunization in absence of adjuvant induce IL-10 production by CD4+ cells and failed to protect mice against challenge infection.Acta Trop. 2012; 124: 140-146Crossref PubMed Scopus (12) Google Scholar). Clearly, an integrated and complete overview of schistosome glycosylation was so far not available. In this study, we therefore set out to determine the overall schistosome protein- and lipid-linked glycome by analyzing a total of 16 lifecycle stages ranging from cercariae to miracidia. We analyzed the glycoprotein-derived N- and O-glycans as well as the lipid-derived glycans of these life stages by a MALDI-TOF MS-based approach complemented with fragmentation and enzyme degradation studies. Our findings give new insights in the glycobiology of parasite development and parasite–host interaction and contribute to the identification of new potential immune intervention targets. Puerto Rican-strains of S. mansoni maintained in the laboratories of LUMC and Aberystwyth University were used throughout this study. For the N-glycan analysis the protein/glycoprotein samples were obtained from the various life stages by TRIzol (Invitrogen, Paisly, UK) extracted homogenates generated as described before (3.Fitzpatrick J.M. Peak E. Perally S. Chalmers I.W. Barrett J. Yoshino T.P. Ivens A.C. Hoffmann K.F. Antischistosomal intervention targets identified by lifecycle transcriptomic analyses.PLoS. Negl. Trop. Dis. 2009; 3: e543Crossref PubMed Scopus (103) Google Scholar). Parasite preparations for O-glycan and lipid-glycan release were obtained separately as follows. Cercariae collected from Biomphalaria glabrata snails were transferred to prewarmed (37 °C) medium199 (Gibco Life Technologies, Bleiswijk, The Netherlands) containing 10 mm HEPES (Sigma-Aldrich, Zwijndrecht, The Netherlands), 1× antibiotic antimycotic solution (Sigma-Aldrich) and 15 μm l-glutamine (Sigma-Aldrich) to induce transformation. After 20 min incubation at 37 °C and 5% CO2 schistosomula were separated from loose tails by orbital shaking. Schistosomula were collected and cultured for 3, 24, 48, and 72 h at 37 °C and 5% CO2 in the same medium or for 9 days in this medium supplemented with erythrocytes (10 μl of packed erythrocytes/200 μl medium, refreshed every 24 h). Adult worms and eggs were obtained from hamsters 7 weeks after infection, as described (30.Dalton J.P. Day S.R. Drew A.C. Brindley P.J. A method for the isolation of schistosome eggs and miracidia free of contaminating host tissues.Parasitology. 1997; 115: 29-32Crossref PubMed Scopus (109) Google Scholar). Mature and immature eggs were isolated by Percoll gradient centrifugation (31.Pellegrino J. Oliveira C.A. Faria J. Cunha A.S. New approach to the screening of drugs in experimental schistosomiasis mansoni in mice.Am. J. Trop. Med. Hyg. 1962; 11: 201-215Crossref PubMed Scopus (203) Google Scholar). Miracidia were obtained from eggs hatched in distilled water and collected as previously described (30.Dalton J.P. Day S.R. Drew A.C. Brindley P.J. A method for the isolation of schistosome eggs and miracidia free of contaminating host tissues.Parasitology. 1997; 115: 29-32Crossref PubMed Scopus (109) Google Scholar). All parasite isolates were subjected to extraction by potter homogenization in chloroform, methanol (MeOH), and water (13:7:4). The upper phase of the extraction was removed after sonication and centrifugation and replaced by the same volume of 50% MeOH. These steps were repeated twice, however, after the last removal of the upper phase the proteins were pelleted by adding an excess amount of 100% MeOH and centrifugation. Pellets were washed three times with MeOH, dried under a flow of nitrogen, and used for O-glycan release. For glycolipid isolation, the combined upper phases from the chloroform-methanol extraction procedure were applied to reversed phase (RP) C18-cartridges (500 mg; JT Baker, Phillipsburg, NJ). Combined flow-through and wash fractions (10 ml water) were applied to a second C18-cartridge, and glycolipids were eluted from both cartridges with 5 ml chloroform/MeOH/water (10:10:1) and dried combined under a flow of nitrogen. Protein extracts were potter homogenized in PBS with 1.3% SDS and 0.1% β-mercaptoethanol. Homogenized proteins were denatured at 60 °C for 10 min. After cooling down, 1.3% Nonidet P-40 Substitute (Sigma-Aldrich) was added. N-glycans except those with Fucα1–3 modified core structures, were released by adding PNGase F (17 mU, Roche Diagnostics, Almere, The Netherlands) and incubation for 24 h at 37 °C. To isolate released glycans, the incubation mixture was applied to a C18 RP-cartridge. The combined flow-through and wash fraction was subsequently applied to a carbon cartridge (150 mg Carbograph; Grace, Deerfield, IL), washed with milliQ, and glycans were eluted with subsequent addition of 25% acetonitrile (AcN) and 50% AcN/0.1% trifluoroacetic acid (TFA). Proteins remaining on the C18-cartridge were retrieved by applying 30% AcN containing 0.1% TFA followed by 60%AcN/0.1%TFA and dried. The protein fraction was dissolved in PBS and incubated overnight at 37 °C while shaking in the presence of trypsin-coated Sepharose, prepared following the manufacturers protocol (GE Healthcare, Diegem, Belgium), to create tryptic peptides/glycopeptides. The supernatants were removed, dried, and taken up in 1 m sodium acetate pH 4.5, before addition of PNGase A (0.5 mU; Roche Diagnostics). Digestion was continued for 48 h at 37 °C and the PNGase A released glycans were purified as described for the PNGase F-released glycans. Protein pellets obtained after chloroform–methanol extraction of parasite homogenates were subjected to reductive β-elimination. The dried samples were taken up in 1 m sodium borohydride, 0